Álvaro Siza: caligrafia concreta - Martins, Alexandre Augusto (2020)
This study examines and explains Álvaro Siza's work and journey, especially regarding the interface between design thinking and the constructed building. It justifies the choice by this architect because he understands that his projective positioning, critical and reflective, which takes space as a resource capable of being molded or modeled, construction as a concrete manifestation of his own artistic ability and architecture as a tangible phenomenon placed at the service of people. As a research hypothesis, this thesis considers the fact that the buildings Álvaro Siza designs materialize his way of thinking an architecture based on a set of correlated conceptual variables: focus on human being, attention to the local context and appreciation of materiality. It situates the architectural course of Álvaro Siza in the history of Portuguese architecture from the mid-twentieth century onwards, relating his projects to some of the political, social and cultural circumstances of the country. It stresses that it is through the genealogy of his work that it is possible to understand an architectural practice that is supported by mediation, balance, pragmatism and the combination, adjustment or harmonization with preexistences. These, although sometimes without patrimonial or monumental value, are respected and considered as basic subsidy to the project. It understands that Siza’s creative exercise considers, in a very particular and characteristic way, a set of negotiations between means and ends, opportunities and choices, materials and forms. It argues that in the experience of built architecture it is possible to perceive the essence of his projects, the consistency of his ideas and Siza's ability to respond positively to the requirements of each new project conceived. It adopts as an investigative procedure the inferential method of Baxandall (2006) articulated to bibliographic and field research. Thereby, elects the Viana do Castelo Municipal Library (2008) and the Nadir Afonso Museum of Contemporary Art (2016), both visited in 2019, for a more detailed design, circumstantial and constructive analysis, namely in relation to the reasons for the orders, to the drawings as indispensable instruments to the project, to the relations with the surrounding spaces, to the formal and material choices, to the structural and constructive systems and to the analogies with other works of his own. It concludes that, over the years, Álvaro Siza has perfected an architectural calligraphy that continues to represent his style or his very own and peculiar way of making architectural projects, and that is enshrined in a continuous experimentation, in the belief that there are no pre-established rules, because always propitious to the combination of design demands and signals provided by the real world. An architecture that does not surrender to contemporary aesthetic manipulation, since it is valued by its own plastic logic, always designed to offer people spaces to be experienced and not just contemplated. An architecture in which matter can be understood as the element that transforms the project’s idea into a tangible element, and for that very reason anticipates the possibilities of existence and resistance in the physical world, thus validating its own raison d'être.